Achieving integration: A dual pathway model of supply chain orientation and organizational identification. Issue 4 (11th June 2018) - Robinson, Jessica L.; Manrodt, Karl; Murfield, Monique Lynn; Boone, Christopher A.; Rutner, Paige
Abstract : Purpose: The purpose of this paper is to propose and test a dual pathway model whereby addressing the question, "What are the effects of supply chain orientation and organizational identification on internal integration and supplier integration?". Design/methodology/approach: A survey design was performed to collect data from supply chain professionals regarding their organization's supply chain orientation (SCO), organizational identification (OI) and achieved states of both internal and supplier integration. Partial least squares-structural equation modeling was performed to test the dual mediating pathways. Findings: The results show that internal integration partially mediates relationships between SCO and supplier integration and for OI and supplier integration. In comparing the mediating effects to test competing theories, the SCO path yields stronger complementary partial mediation. This supports the proposition that SCO and OI mutually exist within an organization and influence achieved integrative behaviors. Additionally, results suggest the behavioral spillover effect exists for an internally integrated organization that has also achieved supplier integration. Originality/value: This research makes several contributions to extant literature, including finding that SCO contributes to levels of achieved integration. Also, this research theoretically integrates literature on the social dilemma associated with supplier integration and the behavioral spillover effect, suggesting that SCO allows for positive internal integrative behaviors to spillover to integrated suppliers. Finally, this research contributes to research on OI by finding achieved integration is an outcome, which refutes a dominate theory that explains OI facilitates negative behaviors toward external organizations.